Hydrogen Generation: Metal–Organic Framework Templated Porous Carbon‐Metal Oxide/Reduced Graphene Oxide as Superior Support of Bimetallic Nanoparticles for Efficient Hydrogen Generation from Formic Acid (Adv. Energy Mater. 1/2018). Issue 1 (5th January 2018) - Song, Fu‐Zhan; Zhu, Qi‐Long; Yang, Xinchun; Zhan, Wen‐Wen; Pachfule, Pradip; Tsumori, Nobuko; Xu, Qiang
Abstract : A metal–organic framework derived zirconia/porous carbon/reduced graphene oxide (ZrO2 /C/rGO) nanocomposite as a superior support of bimetallic nanoparticles is reported in article number1701416 by Qiang Xu and co‐workers. The monodispersed PdAg NPs immobilized on ZrO2 /C/rGO exhibit remarkable catalytic activity for hydrogen production from formic acid under mild conditions, rendered by the strong synergistic effect between metal NPs and support.